ID 316 – EEG resting-state directed connectivity in temporal lobe epilepsy vs healthy controls. Issue 3 (March 2016) - Coito, A.; Plomp, G.; Abela, E.; Iannotti, G.R.; Thomschewski, A.; Höller, Y.; Trinka, E.; Wiest, R.; Seeck, M.; Michel, C.; Vulliemoz, S.
Abstract : Using high-density EEG, we investigated resting-state directed brain connectivity independent from interictal epileptiform discharges (IED) in left and right temporal lobe epilepsy (LTLE and RTLE) compared to healthy controls. Twenty LTLE, 20 RTLE patients and 20 healthy controls underwent a resting-state high-density EEG. Source activity free of IED was obtained for 82 regions of interest (ROI). Granger-causal modeling was applied to the source signal of all ROIs to estimate the summed outflow (SO) from each ROI (to all others) and pair-wise connectivity between ROIs. Correlations with the duration of the disease were computed. In all regions and groups, SO peaked in the alpha band.Consistent across frequency bands and groups, the highest SO occurred in the hippocampus, amygdala, parahippocampus, posterior cingulate cortex (PCC) and anterior cingulate cortex (ACC). The strongest connections in controls were from PCC, while in both patient groups these were from ipsilateral hippocampus. In RTLE, disease duration was negatively correlated to SO in bilateral amygdala and contralateral hippocampus, olfactory and rectus. No correlation was found in LTLE. We identified connectivity impairments in regions of the Default Mode Network. RTLE was more contralaterally affected than LTLE. These network abnormalities could help identify patients when IED cannot be detected.